2012
DOI: 10.1080/17470218.2012.677048
|View full text |Cite
|
Sign up to set email alerts
|

The perception of attractiveness and trustworthiness in male faces affects hypothetical voting decisions differently in wartime and peacetime scenarios

Abstract: Facial appearance of candidates has been linked to real election outcomes. Here we extend these findings by examining the contributions of attractiveness and trustworthiness in male faces to perceived votability. We first use real faces to show that attractiveness and trustworthiness are positively and independently related to perceptions of good leadership (rating study). We then show that computer graphic manipulations of attractiveness and trustworthiness influence choice of leader (experiments 1 and 2). Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 45 publications
5
79
2
Order By: Relevance
“…Consistent with the existence of this trade-off, a range of studies have all found an enhanced preference for masculine and dominant-looking leaders and political candidates in times of threat from outgroups or war (Hall, Goren, Chaiken, & Todorov, 2009;Little, Burriss, Jones, & Roberts, 2007;Little, Roberts, Jones, & DeBruine 2012;Spisak, Dekker, Krüger, & van Vugt, 2012;Spisak, Homan, Grabo, & van Vugt, 2012). In such coalitional "games against people," collective action is vital.…”
Section: Trade-offs In Followership Decisionsmentioning
confidence: 92%
“…Consistent with the existence of this trade-off, a range of studies have all found an enhanced preference for masculine and dominant-looking leaders and political candidates in times of threat from outgroups or war (Hall, Goren, Chaiken, & Todorov, 2009;Little, Burriss, Jones, & Roberts, 2007;Little, Roberts, Jones, & DeBruine 2012;Spisak, Dekker, Krüger, & van Vugt, 2012;Spisak, Homan, Grabo, & van Vugt, 2012). In such coalitional "games against people," collective action is vital.…”
Section: Trade-offs In Followership Decisionsmentioning
confidence: 92%
“…Specifically, it asked subjects to indicate "How well does each word or phrase describe your preferred leader?" coded on a 7-point scale from "not well at all" (1) to "extremely well" (7). Ten characteristics were randomly presented: athletic, attractive, competent, dependable, dominant, friendly, intelligent, physically fit, physically imposing or intimidating, and physically strong.…”
Section: Resultsmentioning
confidence: 99%
“…A masculine face is reliably associated with perceptions of being dominant and with actual aggressive and dominant behavior (Carré, McCormick, & Mondloch, 2009;Geniole, Keyes, Mondloch, Carré, & McCormick, 2012;Loehr & O'Hara, 2013;Stirrat & Perrett, 2010;Trebický, Havlícek, Roberts, Little, & Kleisner, 2013). Correspondingly, a series of studies have found that leaders with more masculine faces are preferred among subjects who are primed with war or between-group conflict scenarios, while subjects who are primed with peace or cooperation scenarios tend to prefer leaders with more feminine faces (Spisak, Dekker, et al, 2012a;Spisak, Homan, et al, 2012b;Laustsen & Petersen, 2015;Little, Burriss, Jones, & Roberts, 2007;Little, Roberts, Jones, & DeBruine, 2012;Re, DeBruine, Jones, & Perrett, 2013). Under conflict, individuals prefer a leader who can enforce collective action against the enemy.…”
Section: Followership Decisions: the Role Of Context And Perceptionsmentioning
confidence: 99%